Typical Skyrmions Versus Bimerons: A Long-Distance Competition in Ferromagnetic Racetracks - Altbir-Drullinsky, D (American Physical Society, 2020)
During the last years, topologically protected collective modes of magnetization have called much attention. Among these, skyrmions and merons have been objects of intense study. In particular, topological skyrmions are structures with an integer skyrmion number Q while merons have a half-integer skyrmion charge q. In this paper, we consider a Q=1 skyrmion, composed of a meron and an antimeron (bimeron), displacing in a ferromagnetic racetrack, disputing a long-distance competition with its more famous counterpart, the typical Q=1 cylindrically symmetrical skyrmion. Both types of topological structures induce a Magnus force, and then they are subject to the skyrmion Hall effect. The influence of the Dzyaloshinskii-Moriya interaction DMI present in certain materials and able to induce DMI skyrmions is also analyzed. Our main aim is to compare the motions (induced by a spin-polarized current) of these objects along with their own specific racetracks. We also investigate some favorable factors which are able to give breath to the competitors, impelling them to remain in the race for longer distances before their annihilation at the racetrack lateral border. An interesting result is that the DMI skyrmion loses this hypothetical race due to its larger rigidity. © 2020 American Physical Society.